Refined clothespin relocation test and assessment of motion. (June 2017) - Hussaini, Ali; Kyberd, Peter
Background: Advancements in upper limb prosthesis design have focused on providing increased degrees of freedom for the end effector through multiple articulations of a prosthetic hand, wrist and elbow. Measuring improvement in patient function with these devices requires development of appropriate assessment tools. Objectives: This study presents a refined clothespin relocation test for measuring performance and assessing compensatory motion between able-bodied subjects and subjects with upper limb impairments. Study design: Comparative analysis. Methods: Trunk and head motions of 13 able-bodied subjects who performed the refined clothespin relocation test were compared to the motion of a transradial prosthesis user with a single degree of freedom hand. Results: There were observable differences between the prosthesis user and the able-bodied group. The assessment used provided a clear indication of the differences in motion through analysis of compensatory motion. Conclusion: The refined clothespin relocation test provides additional benefits over the standard clothespin assessment and makes identification of compensatory motions easily identifiable to the researcher. While this article establishes the method for the new assessment, further validation will need to be performed with more users. Clinical relevance: The refined test provides a more defined structure for the trajectory of the hand/terminal device than the standard protocol for the clothespin relocation test. This will help researchers interested in motion studies of limb segments to efficiently compare and analyse motion between able-bodied and prosthesis user groups.